2021
DOI: 10.3390/v13091858
|View full text |Cite
|
Sign up to set email alerts
|

The Clonal Expansion Dynamics of the HIV-1 Reservoir: Mechanisms of Integration Site-Dependent Proliferation and HIV-1 Persistence

Abstract: More than 50% of the HIV-1 latent reservoir is maintained by clonal expansion. The clonally expanded HIV-1-infected cells can contribute to persistent nonsuppressible low-level viremia and viral rebound. HIV-1 integration site and proviral genome landscape profiling reveals the clonal expansion dynamics of HIV-1-infected cells. In individuals under long-term suppressive antiretroviral therapy (ART), HIV-1 integration sites are enriched in specific locations in certain cancer-related genes in the same orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…This is because they are at higher risk of elimination by cytopathic effects or immune responses after reactivation (at least some Ψdefective proviruses can produce HIV proteins 71 and even virions 72 ). As not all members of a clone will reactivate upon stimulation 73,74 , expansion enhances the likelihood that at least some members will persist 75 . In contrast, grossly defective proviruses rely less on clonal expansion for survival, as their risk of elimination is inherently lower due to limited or no viral antigen presentation 21,53 .…”
Section: Discussionmentioning
confidence: 99%
“…This is because they are at higher risk of elimination by cytopathic effects or immune responses after reactivation (at least some Ψdefective proviruses can produce HIV proteins 71 and even virions 72 ). As not all members of a clone will reactivate upon stimulation 73,74 , expansion enhances the likelihood that at least some members will persist 75 . In contrast, grossly defective proviruses rely less on clonal expansion for survival, as their risk of elimination is inherently lower due to limited or no viral antigen presentation 21,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Although different barcodes themselves may not influence cells, different VISs may. For example, aberrant self-renewal arises when using lentiviral vectors (Espinoza et al, 2019) and different VISs of HIV have been shown to affect cellular proliferation rates (e.g., if the VIS is near an oncogene) Yeh et al (2021). Besides the non-neutrality, we have also neglected stochastic or variable proliferative potential L and the time course of the HSC homing and engraftment into the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…HPV integrations into introns and exons of RAD51 paralog B (RAD51B), a gene encoding a protein with DNA-repair and apoptotic functions, might indicate that this tumor-suppressor gene is disrupted by HPV integration [34]. However, for HIV-1, integration-dependent induction of proliferation appears to have a small overall contribution to clonal expansion [6,87], as recently reviewed elsewhere [88]. Similar to BACH2, the other RIGs of HIV-1 (STAT5B, MKL2, MKL1, IL2RB, MYB, and POU2F1) show enrichment for HIV-1 integrations in the same orientation as host gene transcription and into specific introns in PLWH [4,8,10,87,89,90].…”
Section: Box 2 Proliferation As a Direct Consequence Of Hiv-1 Integra...mentioning
confidence: 99%
“…This indicates that HIV-1 integration into those RIGs might provide a fitness advantage to cells [4,8,10,87,89,90]. Additional evidence for the functional importance of HIV-1 RIGs comes from their over-representation in mouse models compared with in vitro [88,91,92], and the accumulation of cells with integrations in these seven genes in response to ART [4,8,10,87,89,90]. Human T cell lymphotropic virus type 1 (HTLV-1): a deltaretrovirus that causes latent infection but can reactivate to cause various pathologies later on, including adult T cell lymphoma in ~10% of infected individuals.…”
Section: Box 2 Proliferation As a Direct Consequence Of Hiv-1 Integra...mentioning
confidence: 99%